Ética solidária: um estudo da ação religiosa e ética da Liga das Senhoras Católicas de São Paulo, nos princípios de Emmanuel Levinas - Santana, Maria Angelica (2007)
In this work we aboard the face as icon of the solidary ethics and the responsibility on the other, in accordance with the theory of Emmanuel Levinas. Ahead of the face of the Other, the people discover him responsible and the Infinite it comes to the idea. Philosophically, Levinas perceives that the occidental thought, beginning from the Greek philosophy, developed as domination speech. Of Descartes, Levinas keeps the discovery of the idea of the infinite, taking as Metaphysical orientation for its ethics. Levinas conserves in his philosophy influences of the Husserlian phenomenological method and the Heideggerian analytical existential, however distanced of both essentially. It will be, therefore, of great importance, to discover the ethics in practices of the good. The choice of the Levinasian philosophy in this work considers the contribution that Levinas can us offer in the creation of an ethical language, a simple speech. The construction of ethics based on the alterity breaches the identity of I, but it is clearly, in the direction to see the other as reference for the ethical construction, this does not mean negation of the identity of I. This work inquired the voluntary work, the Levinasian s ethic as a principle of the event of the good and the religious practice of LSCSP through the field study. A LSCSP that in the Christian tradition of the religion, has a solidary life on behalf of the fraternity, idea established for the catholic ladies under the perspective of a society more joust. Levinas does not explain the human fraternity being for the similarity, but for the irrepetível unicity of the other, an equality that breaks the difference, that knows to receive the message from the face of the other. Only from the face, that LSCSP sees the possibility to fulfill the law to love God and the next , as well as for Levinas, the revelation it gives for the face of the next. Justice is born, thus, of the mercy, of the responsibility for the other, recognition of the unicity of LSCSP and the other. The force and originality of the philosophy of Levinas consist of the conjuncture that joins and opens, in the face of Other, where it joins the recognition of God with the recognition of the humanity of the Other